Implementasi Pembatalan Putusan Arbitrase Syariah di Pengadilan Agama - Saifuddin, M.; Hadi, Abdul; Isnawati, Muridah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research is motivated by the important role of Religious Courts in maintaining the integrity of Sharia law through the mechanism for annulling Sharia arbitration awards as regulated in Article 70 of Law Number 30 of 1999. Although Sharia arbitration is legally recognized as a final and binding alternative dispute resolution (ADR), judicial oversight is still needed to ensure that arbitration awards do not conflict with the principles of Islamic justice. The purpose of this study is to analyze the implementation of annulling Sharia arbitration awards in Religious Courts and to identify the challenges faced in its implementation. The method used is qualitative research with a juridical-empirical approach, through interviews with seven judges from six work units of the Religious Courts and document studies of related decisions and regulations. The results of the study indicate that cases of annulling Sharia arbitration are still rare due to low public understanding and minimal synergy between BASYARNAS and the Religious Courts. A key finding indicates that judges assess annulments based on formal and material aspects, as well as their compliance with sharia principles, and base their decisions solely on limited reasons as stipulated by law. The implications of this research emphasize the need to improve the capacity of judges and provide public outreach so that this annulment mechanism can function effectively as a means of upholding substantive justice and protecting the values ​​of maqasid al-shari'ah in Islamic economic law.